Qualitative study of primary care clinicians' views on point-of-care testing for C-reactive protein for acute respiratory tract infections in family medicine. Issue 1 (25th January 2017) - Hardy, Victoria; Thompson, Matthew; Keppel, Gina A; Alto, William; Dirac, M Ashworth; Neher, Jon; Sanford, Christopher; Hornecker, Jaime; Cole, Allison
Abstract : Objective: To explore clinicians views of the barriers and facilitators to use of C-reactive protein (CRP) point-of-care tests (POCT) in US family medicine clinics for the management of acute respiratory tract infections (ARTIs) in adults. Setting: Five family medicine clinics across two US states. Participants: 30 clinicians including 18 physicians, 9 physician residents, 2 physician assistants and 1 nurse practitioner, took part in the study. Design: A qualitative study using a grounded theory approach to thematically analyse focus group interviews. Results: These clinicians had limited access to diagnostic tests for patients with ARTI, and very little knowledge of CRP POCT. Three major themes were identified and included the potential clinical role of CRP POCT, concerns related to implementing CRP POCT and evidence needed prior to wider adoption in family medicine. Clinicians believed CRP POCT could support decision-making for some presentations of ARTIs and patient populations when used in conjunction with clinical criteria. Clinicians had concerns about possible overuse and inaccuracy of CRP POCT which they believed might increase antibiotic prescribing rates. Other concerns identified included integration of the test with clinic workflows and cost-effectiveness. Conclusions: Clinicians stand at the forefront of antibiotic stewardship efforts, but have few diagnostic tests to help them confidently manage ARTIs. CRP POCT may facilitate some aspects of clinical practice. Incorporating CRP POCT with clinical guidelines may strengthen utility of this test, when there is diagnostic uncertainty.